Type B pigmentary demarcation lines in a pregnant white woman. - Garofalo, L. (European Journal of Pediatric Dermatology, 2019)
Pregnancy can induce pigmentary changes that can frighten the patient and sometimes the physician: among these changes the hyperpigmentation of previous melanocytic nevi, melasma, linea nigra, secondary areola and pigmentary demarcation lines (PDL) should be remembered; except melasma the other pigmentary changes regress after pregnancy (1). PDL have been divided into various types according to the site affected: type B affects the postero-medial surface of the lower limbs. PDL are frequent in the black population, but they are exceptional in whites. The incidence of PDL in black children is similar to that of adults and these lines have also been demonstrated in the black newborn confirming the precociousness of their appearance (2). Type B is frequently associated with pregnancy, especially with the subsequent pregnancies, being found in 14% of black pregnant women but not in white ones (2).